SELF-ASSESSMENT OF PROFESSIONAL COMPETENCY OF SUPERVISORS OF LATVIA - Kāpiņa, Lelde; Mārtinsone, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In 2019, a new Professional Standard of Supervisor of Latvia was developed and adopted, defining and describing the supervisor's professional competencies. It was necessary to find out whether supervisors who have been certified over the past five years and come from a different background recognize the importance of defined competencies. The aim of this study was to identify the self-assessment of the importance and attainability of professional competence of certified supervisors of Latvia. Two stage mixed method research design was used: (1) qualitative document analysis and expert study in order to develop a questionnaire; (2) quantitative online survey of professional competence of certified supervisors. Supervisors evaluated the importance and attainability of 34 professional competencies on a 5-point Likert scale. For data analysis the descriptive statistical methods, Kolmogorov-Smirnov test and Wilcoxon signed-rank test were used. The study indicated high importance of professional competence (22 of 34 competences as very important and 12 as rather important). The indicators of the attainability of professional competence varied from average to fully attainable, but most (28 of 34 competences) were estimated as mostly attainable. The results showed statistically significant differences between the evaluations of importance and attainability in 17 professional competences. The least important and the least attainable competence was “Ability to carry out research activities for the development of supervision theory and methods”. This study shows that Latvian certified supervisors consider most of defined professional competencies as very important and mostly attainable.